Role of mantle-derived magma in genesis of early Yanshanian granites in the Nanling Range, South China: in situ zircon Hf-O isotopic constraints - Li, XianHua; Li, WuXian; Wang, XuanCe; Li, QiuLi; Liu, Yu; Tang, GuoQiang (Science China. Earth sciences, 2009)
Although a number of petrographic observations and isotopic data suggest that magma mixing is common in genesis of many granite plutons, it is still controversial whether the mantle-derived magmas were involved in granites. We carried out in this study a systematic analysis of in situ zircon Hf-O isotopes for three early Yanshanian intrusions dated at ca. 160 Ma from the Nanling Range of Southeast China. The Qinghu monzonite has very homogeneous zircon Hf-O isotopic compositions, εHf(t) =11.6±0.3 and δ18O=5.4‰±0.3‰. In combination with whole-rock geochemical and Sr-Nd isotopic data, the parental magma of the Qinghu monzonite were likely derived from the partial melting of recently-metasomatized, phlogopite-bearing lithospheric mantle without appreciable crustal contamination. The Lisong and Fogang granites and the mafic microgranular enclaves (MME) within the Lisong granites have a wide range of zircon Hf-O isotopic compositions, with Hf and O isotopes being negatively correlated within each pluton. The Lisong MMEs were crystallized from a mantle-derived magma, similar to the parental magma of the Qinghu monzonite, with small amount of crustal assimilation. The Lisong and Fogang granites were formed by reworking of meta-sedimentary materials by mantle-derived magmas and mixing of the mantle-and sediment-derived melts to varying degrees. It is thus concluded that these two Yanshanian granites in the Nanling Range were formed associated with growth and differentiation of continental crust.